Enhancement of application model for substation site selection - Baharuddin I.N.Z.; Roslan R.; Omar R.C.; Zulkarnain M.S.; Wahab W.A.; Solemon B. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
The existing ESASIRF program (Transmission Line Route Selection Application Model and Development of Environmental Sensitive Area (ESA) Safe and Intelligent Route Finder (ESASIRF) and integration with PLS-CAD) does not cover substation selection and environmental protection. It focuses only on an assessment of the risk of landslides concerning the proposed route of transmission. This study presents the potential of an integrated system using the Geographical Information System (GIS) and Remote Sensing techniques in substation selection to develop an automatic and intelligence method for substation planning in this specific delicate area of the environment. During the selection of the proposed substation, a social impact assessment was also included in this research by defining requirements, problems as well as suitable mitigation measures. With this research, all spatial data for South Putrajaya is acquired and the previous system can be fully utilized. Spatial data from this research were also used to define soil type and flood-prone areas. Finally, this system will be used to assist TNBs in gazetting by applying sustainable concepts in their Transmission Route and Corridor by following Section 21 and Section 22 ACT 172 1973. BEIESP.